Osteoimmunology in orthodontic tooth movement. (14th August 2014) - Jiang, C; Li, Z; Quan, H; Xiao, L; Zhao, J; Jiang, C; Wang, Y; Liu, J; Gou, Y; An, S; Huang, Y; Yu, W; et al.
<x xml:space="preserve">Abstract</x> The skeletal and immune systems share a multitude of regulatory molecules, including cytokines, receptors, signaling molecules, and signaling transducers, thereby mutually influencing each other. In recent years, several novel insights have been attained that have enhanced our current understanding of the detailed mechanisms of osteoimmunology. In orthodontic tooth movement, immune responses mediated by periodontal tissue under mechanical force induce the generation of inflammatory responses with consequent alveolar bone resorption, and many regulators are involved in this process. In this review, we take a closer look at the cellular/molecular mechanisms and signaling involved in osteoimmunology and at relevant research progress in the context of the field of orthodontic tooth movement.